Macroscopic and Microscopic Diagnostic Features of the potential Herbal Drug Crataegus almaatensis Pojark Endemic in Kazakhstan: potential Herbal Drug Crataegus Almaatensis Pojark Endemic - N. Bekbolatova, Elmira; B. Sakipova, Zuriyadda; V. Kurbatova, Natalya; N. Ibragimova, Liliya; I. Alpysbayeva, Saltanat; T. Kabdenova, Akmaral; Kukula-Koch, Wirginia; Boylan, Fabio (Iranian Journal of Pharmaceutical Sciences, 2018)
This study presents the results of anatomic-morphological examination of vegetative (leaves) and generative (flowers, fruits) organs of the endemic plant Crataegus almaatensis Pojark – family Rosaceae, growing in the foothills of Ile Alatau mountains, Almaty region of the Republic of Kazakhstan. The plant Crataegus almaatensis Pojark was examined during the phenological phase of flowering and fruit ripening periods. The macroscopic and microscopic diagnostic features were established, which will allow for the standardization of this herbal plant in order to ensure its quality, safety, and efficacy and to avoid adulteration, misuse in the process of medicines’ preparation on its basis. For the first time significant diagnostic macroscopic and microscopic features of the dried vegetative and generative organs of Crataegus almaatensis Pojark were described in detail. Currently not much is known about this species and this manuscript brings the information which are studied for the first time, according to the authors’ knowledge.